MENARIK BENANG MERAH HUBUNGAN ACEH DENGAN SULAWESI SELATAN - Juliani, Reni (Universitas Teuku Umar, 2017)
This article aims to show clearly how the actual relationship Aceh and South Sulawesi in the past and the present, so that the resulting discourse that Aceh and South Sulawesi have a thread that is not interrupted by distance and differences that have.This study uses library research method. the results of this study indicate that red thread of Aceh and South Sulawesi relantionship starts with the spice trade relations, then the marital relationship between Sultan Iskandar Muda and Putroe Suni who are descendants of Bugis, so that it ties to the history of the entry of the Islam religion to South Sulawesi. At present, the red thread is never interrupted Good relations are still maintained. The remnants of historical relics such as tombs of Kings of Aceh who are descendants of Bugis are still preserved right in front of the building of Aceh Museum. Beside the marriage between the two ethnics (Aceh and Bugis Makassar) which have occurred in the past, is still going on today. Marriage of two ethnic groups is growing. Thus, a red thread ties between Aceh and South Sulawesi is getting stronger.Â Keywords: Red Thread, Aceh, South Sulawesi.